Sources and contexts of inter-industry differences in technological opportunities: The cases of Argentina and Brazil - Marin, Anabel (2018)
It is widely accepted within the innovation and development literatures that some industries offer higher potential for growth and development than others. The general idea is that industries with high technological dynamism offer higher potential for growth and development. There is still a large element of uncertainty, however, as to which are the most dynamic industries for each country. This paper proposes to use the concept of technological opportunity (TO) to investigate the technological dynamism of manufacturing industries of two Latin American Countries (LACs): Argentina and Brazil. Our results do not support the well-spread idea that traditional industries, in particular those strongly associated with natural resources (NRs), have and create less TOs, and therefore are less dynamic than others. They question, therefore, the adequacy of generic policies aimed at encouraging ‘high-tech’ sectors, and suggest that context-specific research needs to be conducted to identify which are the technologically dynamic industries within each country.